2018
DOI: 10.1186/s12917-018-1406-3
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic network measures reveal the impact of cattle markets and alpine summering on the risk of epidemic outbreaks in the Swiss cattle population

Abstract: BackgroundLivestock herds are interconnected with each other via an intricate network of transports of animals which represents a potential substrate for the spread of epidemic diseases. We analysed four years (2012–2015) of daily bovine transports to assess the risk of disease transmission and identify times and locations where monitoring would be most effective. Specifically, we investigated how the seasonal dynamics of transport networks, driven by the alpine summering and traditional cattle markets, affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 49 publications
2
31
0
Order By: Relevance
“…In the monthly networks, two peaks in the frequency of animal movements were apparent during late spring to early summer and in autumn, which is due to the grazing period. Similar seasonal patterns were described also in other countries with grazing practices (40,51,52). In our cattle movement networks, this seasonal pattern was reflected in all monthly global network measures except diameter and was consistent through time.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In the monthly networks, two peaks in the frequency of animal movements were apparent during late spring to early summer and in autumn, which is due to the grazing period. Similar seasonal patterns were described also in other countries with grazing practices (40,51,52). In our cattle movement networks, this seasonal pattern was reflected in all monthly global network measures except diameter and was consistent through time.…”
Section: Discussionsupporting
confidence: 85%
“…We chose these aggregation windows because it was previously argued that networks aggregated over longer time periods may adequately address chronic or slowly spreading diseases (56). Even though the Slovenian cattle movement network is in general smaller and less active compared to other European cattle trade networks, it shares a number of properties with them, such as similar degree distributions, average shortest path length, and diameter (40,41,51,52,57).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, during this period, we observed an increase in the number of nodes and 386 connections; therefore, a given node would require more steps to reach another farm, within the 387 network which could alone reduce the speed of disease transmission (Vidondo and Voelkl, 388 2018 However, these followed the assumption that movement aggregation would not overestimate or 397 introduce edge biases (Vidondo and Voelkl, 2018). It has been suggested that to some extent, 398 static networks provide useful information about disease related risks (Mohr et al, 2018).…”
Section: ‫ݐ‬mentioning
confidence: 97%